Financial Literacy, Financial Behavior and Financial Attitudes Towards Investment Decisions and Firm Bankruptcy - Rustan DM (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The research objective was to analyze financial literacy, financial attitudes, and financial behavior on investment decisions and MSME bankruptcy. The partial influence of financial literacy, financial attitudes, and financial behavior on MSMEs' bankruptcy through investment decisions. The sampling method used was purposive sampling. The population was 149 MSMEs and a sample of 108 MSMEs. The analysis method used SEM-PLS. The results prove that financial literacy, financial attitudes, and financial behavior partially positively and significantly affect investment decisions and MSME bankruptcy in Makassar City. Financial decisions cannot partially intervene in the influence of financial literacy, financial attitudes, and financial behavior on the potential for bankruptcy of MSMEs in Makassar City.